Promoter Activity-Based Case-Control Association Study on SLC6A4 Highlighting Hypermethylation and Altered Amygdala Volume in Male Patients With Schizophrenia. (19th June 2020) - Ikegame, Tempei; Bundo, Miki; Okada, Naohiro; Murata, Yui; Koike, Shinsuke; Sugawara, Hiroko; Saito, Takeo; Ikeda, Masashi; Owada, Keiho; Fukunaga, Masaki; Yamashita, Fumio; Koshiyama, Daisuke; et al.
Abstract: Associations between altered DNA methylation of the serotonin transporter (5-HTT)-encoding gene SLC6A4 and early life adversity, mood and anxiety disorders, and amygdala reactivity have been reported. However, few studies have examined epigenetic alterations of SLC6A4 in schizophrenia (SZ). We examined CpG sites of SLC6A4, whose DNA methylation levels have been reported to be altered in bipolar disorder, using 3 independent cohorts of patients with SZ and age-matched controls. We found significant hypermethylation of a CpG site in SLC6A4 in male patients with SZ in all 3 cohorts. We showed that chronic administration of risperidone did not affect the DNA methylation status at this CpG site using common marmosets, and that in vitro DNA methylation at this CpG site diminished the promoter activity of SLC6A4 . We then genotyped the 5-HTT-linked polymorphic region (5-HTTLPR) and investigated the relationship among 5-HTTLPR, DNA methylation, and amygdala volume using brain imaging data. We found that patients harboring low-activity 5-HTTLPR alleles showed hypermethylation and they showed a negative correlation between DNA methylation levels and left amygdala volumes. These results suggest that hypermethylation of the CpG site in SLC6A4 is involved in the pathophysiology of SZ, especially in male patients harboring low-activity 5-HTTLPR alleles.